Tribological properties of surface nanocrystalline martensite steel in vacuum. (May 2017) - Fu, Licai; Tan, Pin; Zhu, Jiajun; Yang, Wulin; Li, Deyi; Zhou, Lingping
Abstract: The tribological properties of martensite steel with different grain sizes in vacuum was studied. The surface nanocrystalline martensite steel exhibited lower wear rate but higher friction coefficient than corresponding coarse grained steel in vacuum. The results presented that the tribo-oxidation has been effectively restricted in vacuum. Therefore the mechanical behavior was the main factor of the wear rate variety of martensite steel with different grain sizes. The surface film of martensite steel formed easier as the hardness increased and ductility weakened. So the wear mechanisms of the martensite steel in vacuum changed from plastic deformation and adhesion to adhesion and fracture as the grain size decreased. Highlights: The tribological properties of martensite steel was studied in vacuum. The wear rate reduced but friction coefficient increased as grain size decreased. The mechanical behavior was the main factor for tribological properties in vacuum.